(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The most common cause of visual impairment in patients with diabetic retinopathy is the pathology progression to the proliferative stage which is accompanied by apparent fibrovascular proliferation, development of tractional retinal detachment and/or vitreous hemorrhage. Vascular endothelial growth factor (VEGF) is the most important in the pathogenesis of ocular microvascular changes in diabetes. Purpose: To assess vitreous VEGF levels in the proliferative diabetic retinopathy (PDR) patients not initially treated with anti-VEGF agents, depending on the general clinical status and ocular status. Material and Methods: Forty-one patients (45 eyes) aged 19 to 81 years with neovascular glial PDR and epiretinal membrane with a marked proliferative component were involved in the study. Each patient underwent a 25G three-port vitrectomy during which a vitreous specimen was collected. Vitreous VEGF levels were determined by a three-step enzyme-linked immunosorbent assay. Results: We managed to assess total vitreous VEGF levels in 44 of the 45 eyes. Patients with PDR had elevated total vitreous VEGF levels, with a mean value of 757.69 ± 117 pg/ml, confirming the involvement of VEGF in pathological intraocular angiogenesis. There was a significant difference in vitreous VEGF levels between PDR patients with a fibrovascular membrane with a marked proliferative component (997.0±151.8 pg/ml) and those with a fibrovascular membrane with a moderate proliferative component (244.9 ± 53.7 pg/ml) (F = 10.3; р = 0.0025).